Statement by The Managing Director on the Work Program of The Executive Board : December 11, 2019. (Policy Papers; Policy Paper ;, 2020)
This Work Program (WP) translates the strategic directions and policy priorities laid out in the Fall 2019 Global Policy Agenda (GPA) Update and the International Monetary and Financial Committee Communique into an Executive Board agenda from November 2019 to October 2020, focusing on the next six months. Its main policy priorities and deliverables are as follows: -- Turn evidence-based analysis into actionable policy recommendations to make economies more resilient and inclusive -- Contribute to improving the multilateral system and upgrading international cooperation to bring the benefits of integration to all -- Modernize the Fund's policy toolkits to meet the challenges of a fast-changing world -- Safeguard the Fund's financial strength and undertake an ambitious internal modernization agenda.